FeCl3 Intercalated Microcrystalline Graphite Enables High Volumetric Capacity and Good Cycle Stability for Lithium‐Ion Batteries. Issue 4 (28th March 2019) - Sun, Yali; Han, Fei; Zhang, Chengzhi; Zhang, Fuquan; Zhou, Dianwu; Liu, Hongbo; Fan, Changling; Li, Xuanke; Liu, Jinshui
Abstract : To achieve a high volumetric capacity, both high tap density and high gravimetric capacity should be considered in one electrode. Herein, microcrystalline graphite (MG), a type of excellent graphite host, is proposed for the large‐scale preparation of FeCl3 ‐intercalated graphite intercalation compounds (GICs) to simultaneously meet the requirements of high tap density (0.95 g cm −3 ) and high gravimetric capacity (905 mAh g −1 ). FeCl3 ‐intercalated MG achieves the integration of isotropic orientation structure, amorphous carbon ingredients between graphite grains, and crumpled graphite layers, thus effectively buffering structure expansion and suppressing the dissolution of soluble FeCl3 guest and LiCl discharge products. In a lithium‐ion cell, the anode shows a high volumetric capacity of 859 mAh cm −3 and a stable cycle performance for lithium‐ion storage. More importantly, the influence of microstructure features of GICs on their electrochemical properties is demonstrated, which may be of great value to better design and prepare other GIC anodes for high volumetric capacity and good cycle stability. Abstract : FeCl3 ‐intercalated microcrystalline graphite achieves the integration of isotropic orientation structure, amorphous carbon ingredient between graphite grains, and crumpled graphite layers, thus effectively buffering structure expansion and suppressing the dissolution of soluble FeCl3 guest and LiCl discharge products. In a lithium‐ion cell, the anode shows a high volumetric capacity of 859 mAh cm −3 and a stable cycle performance for lithium‐ion storage.